'It's the organization that is wrong': Exploring disengagement from organizations through leadership development. (April 2020) - Larsson, Magnus; Holmberg, Robert; Kempster, Steve
This research explores the relationship between participation in leadership development programmes and disengagement from the employing organization. Based on repeated interviews with 10 managers participating in an open leadership development programme, our analysis shows that half of the participants reflected a sense of distancing themselves from how their organizations practiced leadership, and for some, an emotional disengagement with their home organization which we see as analogous to changes in social identity. We problematize the role of management and leadership development programmes with regard to the relationship between organizations and employees. A series of paradoxes are reflected in our critique of this relationship. The most prominent in terms of implications is that a successful management and leadership development programme – recognized by employees and employers – can generate dissatisfaction with the home organization as a consequence of the purpose of the programme: to increase confidence and enhanced agency. This paradox has significant implication to the leadership development industry and we explore these implications.